Experimental Verification of a Fuzzy Adaptive Sliding Mode Control Design for IM Speed Control - Sabouni, Boudjema; Makhloufi, Khadidja; Zerikat, Mokhtar; Bouchiba, Bousmaha; Bousserhane, Ismail Khalil (Periodica polytechnica. Electrical engineering and computer science, 2025)
This article aims to develop a fuzzy adaptive SMC technique that incorporates a variable boundary layer and adaptive switching gain for speed control of a three-phase induction motor (IM) drive. The boundary-layer characteristics are chosen to offer the best compromise between control robustness and chattering elimination or reduction. In addition, this technique offers many advantages for uncertain dynamic systems. The chattering phenomenon, a well-known problem in classical SMC, arises when the switching function attracts the state trajectory toward the sliding surface. Several methods and approaches have been tried to eliminate this phenomenon. We propose here an approach that involves fuzzy logic to avoid this undesirable effect so that the stability condition according to Lyapunov is verified. This fuzzy adaptation system associated with the SMC (FASMC) towards the obtained results forms a robust tool for chattering reduction. Finally, an experimental prototype setup tests the robustness of the fully developed control structure. The experimental results obtained from the FASMC for speed IM drives demonstrate the highest effectiveness and robustness when compared to the conventional SMC controller.